Filipino Americans discovering their past for the future (Filipino American National Historical Society, 1994)
An in-depth documentary about the first and second waves of Filipino American immigrants in the United States, and the second generation that followed after the Second World War. Includes oral history excerpts from Benjamin B. Menor, Bruno Tapang, Antonio Rodrigo, Frank Leanio, Chris Mensalves.